Egyptian paediatric kidney transplantation pre-transplant guidance highlights on donor and recipient assessment (R. N. 364) - Clinical Adaptation Group (GAG); Bahia Moustafa; Neveen A. Soliman; Ahmed Badr; Mohamad K. EL-Hatw; Engy A. Mogahed; Mona El Ghamrawy; Noha Shaheen; Khaled M. ElKhashab; Mohamed G. Shouman; Abeer Selim; Sawsan Moselhy; et al. (SpringerOpen, 2024)
Abstract Background Kidney transplantation for chronic kidney disease (CKD) in children is the best treatment option. It needs special medical and surgical expertise highly skilled in management of pediatric age group. Our Egyptian profile for causes of end-stage renal failure (ESRF) in transplanted children reflects prevalence of inherited kidney diseases IKD (43%), urologic causes (26%), glomerulonephritis (GN) (17%), and unknown causes (14%). Renal graft availability remains a great challenge. Aim We need pediatric kidney transplantation (PKT) guideline since children have unique causes for ESRF compared to adults. Their transplant team should be skilled in management of children challenges. Recipients may not have one transplant per life. Long-standing immunosuppression will have its toxicity and need regular monitoring. Lots of data are extracted from adult guidelines lacking paediatric background. Young paediatric nephrologists need short version guidelines rich in educational figures for management plans. Children and their families need Arabic orientation booklets and supportive programmes. National Insurance System sponsors should be guided by National Pediatric Guidelines to minimize the centre's variations. Methods Our National Pediatric Guidelines are evidence based adapted from international four source guidelines with permissions [KDIGO-2020, RA/BTS 2022-2018, EAU 2018] that were appraised with Agree 2 plus tool using PIPOH format health questions. We followed the 'adapted ADAPTE' CPG formal adaptation methodology that consists of three phases and 24 steps and tools. It was registered on the practice guideline registration international guideline registry with a registration number IPGRP-2023-12-27 CN 312. Results Summary includes recommendations for assessment of (1) potential living adult donors for age, medical, surgical, immunologic, familial, metabolic, malignancy, and any donor morbidities and (2) transplant recipient assessment for age, weight, nutritional, psychosocial, immunological, infection states, primary native kidney disease, associated morbidities, the presence of genetic, immunologic, infection, and malignancy risks. Conclusion Pediatric kidney transplantation guidelines aim for better donor, recipient, and graft survival. Recommendations are tailored as adopted or adapted statements from evidence-based source guidelines to suit our local pediatric CKD profile.